Obstacles to Developing Digital Literacy on the Internet in Middle School Science Instruction. (September 2013) - Colwell, Jamie; Hunt-Barron, Sarah; Reinking, David
Obstacles, and instructional responses to them, that emerged in two middle school science classes during a formative experiment investigating Internet Reciprocal Teaching (IRT), an instructional intervention aimed at increasing digital literacy on the Internet, are reported in this manuscript. Analysis of qualitative data revealed that IRT enabled students to explain and demonstrate appropriate strategies for locating and evaluating information on the Internet when they were asked to do so. However, students did not use these strategies or they quickly abandoned them when working independently or in small groups during inquiry projects. Data revealed three obstacles that inhibited efforts to promote consistent, independent use of strategies: the teacher's role in student inquiry, the structure of inquiry projects, and students' previous strategies. Results suggest notable challenges to implementing instruction that inculcates dispositions among middle school students leading to consistent, independent use of appropriate strategies for locating and evaluating information on the Internet. Implications for practitioners, policy makers, and researchers are discussed.